2011
DOI: 10.3389/fimmu.2011.00083
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 Ligand Induces the Generation of CD20+ Plasmablasts and Plasma Cells from CD27+ Memory B-Cells

Abstract: Plasma cells (PCs) have a heterogeneous phenotype in humans. While bone marrow PCs are CD20−CD138+, tonsil PCs are CD20+CD138+/− and peripheral plasmablasts (PBs) are CD20−CD138−. In vitro, PCs are mainly generated by the activation of CD27+ memory B-cells through transient stimulation of CD40, and their phenotype appears similar to that of bone marrow PCs. While CD20 expression is lost at the plasmablastic stage, CD138 expression appears only at the PC stage. Thus, the CD20+CD138± phenotype of tonsil PCs does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
1
20
1
Order By: Relevance
“…However, it is important to note that CD20 1 plasmablasts have been described in tonsils as well as after in vitro differentiation experiments. [14][15][16] Moreover, in agreement with the study of Sushanek et al, 32 we observed low expression of CD20 in the proposed B-1 cells relative to both naive and memory Bcell subsets (as measured by the median fluorescence intensities by flow cytometry; data not shown). The higher expression levels of both CD43 and CD27 and the lower expression levels of CD20 relative to memory B cells (and comparable to plasmablasts, this work, and Verbinnen et al 11 ) indicate a pre-plasmablastic phenotype.…”
Section: Cd69supporting
confidence: 80%
See 1 more Smart Citation
“…However, it is important to note that CD20 1 plasmablasts have been described in tonsils as well as after in vitro differentiation experiments. [14][15][16] Moreover, in agreement with the study of Sushanek et al, 32 we observed low expression of CD20 in the proposed B-1 cells relative to both naive and memory Bcell subsets (as measured by the median fluorescence intensities by flow cytometry; data not shown). The higher expression levels of both CD43 and CD27 and the lower expression levels of CD20 relative to memory B cells (and comparable to plasmablasts, this work, and Verbinnen et al 11 ) indicate a pre-plasmablastic phenotype.…”
Section: Cd69supporting
confidence: 80%
“…[14][15][16][17] We therefore further characterized the proposed human B-1 cells and compared them directly with circulating CD20 2 plasmablasts. Spontaneous antibody production of different isotypes as well as the induced production of antigen-specific antibodies after vaccination with a TD antigen did not reveal differences between the proposed B-1 cells and genuine plasmablasts.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, other groups reported lipopolysaccharide and CpG‐ODN increase and are significant in cirrhotic patients and murine models . Increased TLR9 expression of memory B cells could enhance sensitivity to CpG‐ODN, a well‐described B‐cell stimulant previously shown to induce CD27 + B‐cell differentiation into plasmablasts after B‐cell receptor cross‐linking or cytokine activation …”
Section: Discussioncontrasting
confidence: 59%
“…Putative pre-plasmablasts in tonsillar tissue were described as CD20 negative and CD38 low expression; however, these B cells were looked for but not found in peripheral blood (39). CD20 + B cells that express a high level of CD38 have been generated following memory B cell culture with a CpG-containing cytokine cocktail, but it is not clear whether such putative pre-plasmablasts occur normally or circulate (40, 46). A minor subpopulation of peripheral blood plasma cells that is CD20+ has been noted in a study post-immunization, but little is known about these cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Most prominently, it has been suggested that CD20 + CD27 + CD43 + B-1 cells represent plasmablasts that, like B-1 cells, spontaneously secrete antibody, or represent B cells related to plasmablasts, such as pre-plasmablasts (36). It should be noted that, to date, pre-plasmablasts have been poorly defined, and/or undetectable in peripheral blood (38-40). Overall, the existence of a distinct, circulating B-1 cell population in humans, which is separate from immunoglobulin-secreting pre-plasmablasts/plasmablasts remains controversial.…”
Section: Introductionmentioning
confidence: 99%